2018
DOI: 10.1007/s10953-018-0794-0
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Metastable Equilibria for Solar Evaporation of Brines and Solubility Determination: A Critical Discussion

Abstract: Within the last two decades, a large number of articles were published that report, as the authors claim, 'metastable phase equilibria', or 'metastable solubilities'. The main objective of these studies was to carry out experiments under conditions closely meeting those in solar evaporation ponds or industrial evaporation-crystallization processes. Occasionally, such studies were subject to controversial discussion and criticism and the question was raised whether metastable equilibrium data are worth being pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…On the basis of the input of several JCED reviewers, manuscripts using this method are no longer accepted by this Journal. In a recent review, Steiger and Voigt critically discussed this method and concluded that the resulting data are not acceptable as thermodynamic measurements and, in particular, they do not correspond to valid metastable states.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…On the basis of the input of several JCED reviewers, manuscripts using this method are no longer accepted by this Journal. In a recent review, Steiger and Voigt critically discussed this method and concluded that the resulting data are not acceptable as thermodynamic measurements and, in particular, they do not correspond to valid metastable states.…”
mentioning
confidence: 99%
“…Steiger and Voigt also listed typical experimental difficulties in solubility determinations, focusing chiefly on stable and especially metastable equilibria involving oceanic salts and related brine systems. In this editorial, special emphasis will be placed on experimental techniques that are acceptable for JCED publications with an aim to provide guidelines to authors and reviewers.…”
mentioning
confidence: 99%
See 3 more Smart Citations